Using geomorphometric techniques to identify relief patterns in Rio Preto Basin, in the Western Plateau of São Paulo State - Araújo, João Paulo Carvalho; Silva, Francisco Assis Dourado; Nazar, Thallita Isabela Silva Martins (Sociedade & Natureza, 2022)
Geomorphological science benefits greatly from technological advances, such as GIS tools available through free software and the improved accessibility to global or quasi-global planialtimetric databases at a semi-detailed scale. Consequently, there is growing use of geomorphometric techniques applied to geomorphological cartography and optimization of mapping routines using semi-automated, digital methods. In this sense, this study applies a geomorphometric classification based on a Digital Elevation Model to compartmentalize the relief patterns of the Rio Preto basin (BRP). We used three main morphometric parameters to define seven landform patterns, namely, drainage density (DD), roughness concentration index (RCI), and relative elevation (RE) - an approximation of relative relief. The global dissection map (DDxRCI) and RE classes were used to create a classification key for the models and relief types based on theoretical and field knowledge. Despite the apparent simplicity and monotony of the predominantly hilly topography characteristic of the Western Plateau of the state of São Paulo, the results demonstrate a diversity in landform patterns, with planated hilltops and gentle hills (65 % of the study area), topographically favorable to the expansion of regional agricultural; steep undulating hills (9 % of the study area), associated with a higher degree of dissection, where morphodynamic processes predominate over pedogenetic processes; valley bottoms (18 % of the study area), where fluvial dissection predominates; and fluvial plains (8 % of the study area), which are quaternary depositional features located on the valley bottoms. In addition to a morphographic characterization of the study area, this study sheds light on certainsome methodological aspects of the mapping and it is intended to be applied to environmental vulnerability assessment in future activities.